AN INDIVIDUALIZED AND COMPREHENSIVE APPROACH TO TREATING SLEEP PROBLEMS IN YOUNG CHILDREN. Issue 1 (20th February 2013) - Jin, C. Sandy; Hanley, Gregory P.; Beaulieu, Lauren
Abstract We evaluated the effects of assessment‐based interventions on the treatment of sleep problems in 3 young children, 2 of whom had been diagnosed with autism. We used sleep diaries and infrared nighttime video in the child's bedroom to obtain measures of sleep onset, sleep‐interfering behaviors, night waking, total sleep, parental presence, and medication administration each night. We then identified environmental factors that contributed to sleep problems using an open‐ended interview called the Sleep Assessment and Treatment Tool. Individualized treatment packages were designed with the children's parents based on the idiosyncratic results of the assessment. Treatment packages included adjustment of the sleep schedule based on developmental norms and current sleep phases, design of a sleep‐conducive environment, elimination of inappropriate sleep dependencies, and function‐based interventions to decrease sleep‐interfering behaviors by disrupting the contingency between the interfering behavior and its likely reinforcement. A nonconcurrent multiple baseline design across subjects revealed that treatment was effective for all 3 children. In addition, social acceptability measures showed that the parents were satisfied with the assessment process, the treatment, and the amount of behavior change.